The Effectiveness of the E-Ticketing Program in Handling Traffic Violations at the Bandung Police Jurisdiction - Florensia Nirmala Widya Pertiwi (Advances in Police Science Research Journal, 2021)
This research is motivated by the number of traffic violations that occur in the city of Bandung because the density of the population of Bandung is accompanied by the increasing number of motorized vehicles every year but not balanced with road expansion. This kind of condition requires an extra role from the police to take action when pre-emptive and preventive methods are ignored by the public. Action can be carried out by providing administrative sanctions (ticketing) where the implementation of the ticket itself has become more modern in accordance with the development of science and technology, namely the E-Tilang program which has been inaugurated by the Police Corps. This research uses the concept of ticketing, law enforcement, and traffic offenses and uses the theory of legal effectiveness, George R. Terry's management theory, and the deterrent effect theory as the analysis tool. This study uses a qualitative approach and descriptive methods to explain the effectiveness of the E-Tilang program in prosecuting traffic violations at Polrestabes Bandung. Sources of data were obtained through interviews, observations, and document review. The results of the study explained that the kamseltibcar situation was then dominated by traffic jams that spurred offense from motorists. Then the implementation of law enforcement with E-Tilang still faces shortcomings such as members who have not been trained, people who are still unfamiliar with the E-Tilang program, and its implementation in areas that are often seen makes it even more complicated. The factors that influence the effectiveness of the E-Tilang program are internal factors, namely the ability of personnel, attitudes and ethics, sarpras, and socialization, as well as external factors, namely nature and the environment, society, and cooperation with other agencies. Suggestions from researchers so that in the future the implementation of E-Tilang will be more effective is to provide traffic training to all traffic personnel, form an integrated system between the police and the prosecutor's office so that there are no errors in data input so that the process can run faster, and conduct socialization about E- Tickets to the people of Bandung as a whole.